Determination of the effect of chitosan treatment before storage on the storage of mulberry fruits - Pusik, Ludmila; Pusik, Vladimir; Bondarenko, Veronika; Mulienok, Yana; Shubenko, Lidiia; Muliarchuk, Oksana; Cherneha, Andrii; Novikov, Volodymyr; Voitsekhivskyi, Volodymyr (Eastern-European Journal of Enterprise Technologies, 2025)
The study of the preservation of the quality of berry raw materials is becoming relevant due to the value of berries as a food product for dessert and technological purposes in the processing industry. The solution to this issue is the use of edible films and coatings. The problem being solved is to determine safer and more effective technologies for post-harvest treatment of mulberry fruit with chitosan solutions, which will reduce product losses during storage and extend the duration of its consumption. The object of the study is the technology of pre-treatment of mulberry fruit using edible coatings based on chitosan. The subject of the study is mulberry fruit and protective coatings with 0.2 % 0.4 % 0.6 % concentration of chitosan and 0.5 % ascorbic acid. The minimum weight loss of mulberry fruit (2.72 %) and daily losses (0.84 %) during storage were observed after pretreatment with 0.6 % chitosan dissolved in 0.5 % ascorbic acid. The addition of ascorbic acid inhibited the development of Botrytis cinerea by 1.5–2.1 times. There is a close inverse relationship between the yield of marketable products and the concentration of the chitosan solution. An increase in the concentration of chitosan from 0.2 % to 0.6 % reduces natural weight loss, physiological disorders of fruit, and absolute shortage of products. The yield of marketable products increases from 91.7 to 95.1 %. The dry matter content during the storage period decreased by 3.0–6.6 % when treated with an aqueous solution of chitosan and a 2.0–3.5 % solution with ascorbic acid. The lowest losses were observed when treated with 0.6 % chitosan solution and 0.5 % ascorbic acid. A similar pattern was observed for the content of dry soluble substances